Design of Microstrip Antenna Array for Autonomous Vehicles - Noor Qasim Ali Husien; Hassan F.Khazaal Al-khazaali (Wasit Journal of Engineering Sciences)
The utilization of Autonomous vehicles has been rapidly increasing in both civilian and military applications. This is primarily due to their exceptional communication capabilities with ground clients, as well as their inherent properties such as adaptability, mobility, and flexibility. To effectively monitor and control the deployment of Autonomous vehicles, a 5G wireless network can be utilized alongside other devices as user equipment (UE). Through the utilization of a highly directive microstrip patch antenna (MPA) functioning within a dedicated frequency band, the Autonomous vehicle is able to establish effective long-range communication, overcoming signal degradation and minimizing interference from other channels within a confined area. The adoption of MPA is especially advised for Unmanned Aerial Vehicles (UAVs) due to its characteristics such as being lightweight, cost-efficient, small in size, and having a flat structure. This study details the development and simulation of a highly directive single-band 1x2 and 1x4 antenna array designed to operate at a 5.8 GHz frequency specifically tailored for Autonomous vehicle use. To enhance directivity and ensure structural robustness, the Roger RT5880 material has been utilized as a substrate, known for its lower dielectric constant.. The results demonstrate a high gain of 9.16 dBi and 11.4 dBi for the 1x2 and 1x4 antenna arrays respectively, while maintaining a compact size. The simulated 1x4 antenna array was fabricated using the Roger RT5880 material, and this array was tested in the microwave communication's laboratory at College of Engineering, Al-Nahrain University. The antenna presents good results by means of return losses (-26.672 dB) which equivalent to VSWR of 1.098.